Complete chloroplast genome of the wild Japanese Mountain cherry (Prunus jamasakura, Rosaceae). Issue 1 (2nd January 2020) - Yi, Xian-Gui; Chen, Jie; Li, Meng; Zhu, Hong; Sun, Zhong-Shuai; Katsuki, Toshio; Wang, Xian-Rong
Abstract: Prunus jamasakura is a species of Prunus native to eastern Asia. We determined the first complete chloroplast genome of Prunus jamasakura using genome skimming approach. The cp genome was 157, 905 bp long, with a large single-copy region (LSC) of 85, 910 bp and a small single-copy region (SSC) of 19, 123 bp separated by a pair of inverted repeats (IRs) of 26, 436 bp. It encodes 129 genes, including 84 protein-coding genes, 37 tRNA genes, and 8 ribosomal RNA genes. We also reconstructed the phylogeny of Prunus sensu lato using maximum likelihood (ML) method, including our data and previously reported cp genomes of related taxa. The phylogenetic analysis indicated that P. jamasakura is closely related with Prunus speciosa .